Estratégias lúdicas utilizadas no ensino de parasitologia na educação básica - SILVA, Gislene Ferreira da (Universidade Federal do Tocantins, 2024)
Parasitology studies the ecological relationship between two organisms of different species. Parasitic infections are more preeminent in childhood due to poor hygiene habits and the vulnerability of the immune system, which can impair the physical and cognitive development of children and adolescentes. Paying attention to this occurrence, it is possible to seek within the school reality, practices that help in the orientation and prevention of parasitic diseases. Considering the complex biological cycles and terminologies associated with parasitology, the use of playful resources in teaching practice can be a complementary resource to stimulate curiosity and foster students' understanding. Thus, the objective of this research was to verify playful activities that aim to contribute to the teaching of parasitology in basic education between the years 2012 and 2022. To this end, the research consists of an exploratory bibliographic analysis of qualitative nature, for which a bibliographic survey was conducted on the playful activities used in the teaching of parasitology in basic education. We used journal portals such as Scielo Brazil, Bielefeld Academic Search Engine (BASE), Dialnet, WordWideScience, RefSeek, Periódicos Capes, and Google Scholar. The works were selected through the following descriptors: ludic and parasites; parasitology in textbooks; parasitology and school curriculum; teaching learning in parasitology and parasitological games. The search returned a total of 1442 publications, of these, 127 were in the Bielefeld Academic Search Engine (BASE), 9 in Dialnet, 44 in the Periódicos Capes, 30 in Scielo Brazil and in Google Academic 1232 documents. Eighteen papers were selected that fit the objectives to be achieved. It was evaluated that there are several playful activities that can be used in the subject of parasitology that are interactive, fun, participatory, and motivate students, contributing to satisfactory results in learning. It is worth mentioning that all the works found can be applied in other disciplines for teaching various contents.